Dracula [videorecording (Blu-Ray)] - Elfman, Danny (Vertical Entertainment, 2026)
"When a 15th-century prince witnesses the brutal murder of his wife, he renounces God and damns heaven itself. Cursed with eternal life, he is reborn as Dracula, an immortal warlord who defies fate in a blood-soaked crusade to wrench his lost love back from death, no matter the cost. On the verge of reuniting, Dracula is hunted by a relentless priest, sword to end his immortal reign."--